PERGESERAN BAHASA DAN IDENTITAS SOSIAL DALAM MASYARAKAT MINANGKABAU KOTA: STUDI KASUS DI KOTA PADANG - Rina Marnita (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
Minangkabau is a bilingual diglossic community where the Indonesianand Minangkabau languages live side by side with its own communicativefunction. However, during the last three decades, the Indonesian language hasbeen increasingly used not only in public places for formal purposes but alsoat home among family members in daily communication. Working under theframework of Hymes (1964) sociolinguistic ethnography and implementingFishmans (1970) domain theory, a study is conducted in Minangkabau speech community in Padang, the capital city of West Sumatra Province. The study aims to investigate language choice and language attitude of the Minangkabau as well as to examine the socio-cultural determinants motivating the choice and the attitude. It reveals that different age group perform different pattern of language choice; adoloscents speak more Indonesian than teenagers, adults and older speakers. This indicates the language shifting, that is from Minangkabau to Indonesia, to some degree has been in progress in the speech community. Peoples positive attitude toward Indonesian as the language of the educated people has motivated most young families in Padang to choose Indonesian as the frst language of their children. The prestige of nonformal Jakartan Indonesian languages has attracted the youth to use the variety of these languages in their social interaction.Keywords: language choice, language attitude, language shift, social identity,Minangkabau and Padang